PENGELOLAAN PAKAN DAN PENGENDALIAN PENYAKIT LARVA KERAPU TIKUS (Cromileptes altivelis) - Muh. Sulaiman Dadiono; Indra Suryawinata; Rima Oktavia Kusuma (Universitas Cokroaminoto Palopo, 2022)
Larval health is an important problem faced by the hatchery of humback grouper (Cromileptes altivelis). One of the factors that influence larval mortality is feed management and disease control in humback grouper larvae. Methods of data collection is done by means of direct interviews, active participation and observation. Feeding the larvae was started when the larvae were 2 days old with the first feed being Nannochloropsis occulata. Then Rotifera was given when the larvae were 2-4 days old with a density of 5 individuals/ml. Feed in the form of Artemia is given when the larvae are 20 days - 40 days old. Level 1 pellet feed was given when the larvae were 8-10 days old. The disease that often attacks humback grouper larvae is VNN (Viral Nervous Necrosis) with the characteristics of infected larvae are weak movement, larvae float on the surface, decreased appetite and larvae lying on the bottom of the pond. The bacterium that attacks the larvae is Vibrio alginolyticus. Treatment of Vibrio alginolyticus can use antibiotics but has bad side effects. While alternative medicine can use drugs from natural ingredients.